2015
DOI: 10.1093/ecco-jcc/jjv032
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Management, and Course of Cancer in Patients with Inflammatory Bowel Disease

Abstract: Patients with IBD have an increased risk for non-melanoma skin cancer and small bowel cancer. Immunosuppresive therapy is not related to a higher overall risk for cancer or worse tumor evolution in patients who maintain these drugs after cancer diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 34 publications
3
43
0
1
Order By: Relevance
“…We estimated an incidence of 21.7/100,000, which is lower than the incidence in the general Swiss population (NICER, 47.7 for males, 29.5/100,000 for females). Similar results were achieved by a recent Spanish cohort study [23] . This paradoxical result is most likely caused by the fact that the median age of the investigated population was quite low and the incidence of CRC increases with age.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We estimated an incidence of 21.7/100,000, which is lower than the incidence in the general Swiss population (NICER, 47.7 for males, 29.5/100,000 for females). Similar results were achieved by a recent Spanish cohort study [23] . This paradoxical result is most likely caused by the fact that the median age of the investigated population was quite low and the incidence of CRC increases with age.…”
Section: Discussionsupporting
confidence: 90%
“…However, the CESAME cohort study found an incidence similar to the general population [31] . Algaba et al [23] also confirmed this new trend. The suggested regular skin cancer screening in IBD patients may be the reason for this finding.…”
Section: Discussionmentioning
confidence: 68%
“…Eleven articles represented duplicate data 47–52 and we were unable to obtain sufficient information for analysis from 5 studies 53–57 resulting in a final cohort of 16 unique studies 3443, 46, 58–62 (Table 1). There was an equal number of studies in IBD 35, 3942, 46, 58 and RA 34, 36, 37, 43, 60–62 , with 1 study combining both populations 59 and 1 study in psoriasis 62 . Ten studies were population-based 3438, 43, 46, 59, 60, 62 and 12 studies adopted a cohort design 3438, 40, 41, 43, 46, 59, 60, 62 .…”
Section: Resultsmentioning
confidence: 99%
“…Ten studies were population-based 3438, 43, 46, 59, 60, 62 and 12 studies adopted a cohort design 3438, 40, 41, 43, 46, 59, 60, 62 . Three were from North America 40, 58, 59 , twelve from Europe 3439, 4143, 46, 60, 62 , and one from Asia 61 . The included studies investigated a spectrum of prior cancers (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation